Transcriptome profile of halofuginone resistant and sensitive strains of Eimeria tenella - Sun, Pei; Wang, Chaoyue; Zhang, Yuanyuan; Tang, Xinming; Hu, Dandan; Xie, Fujie; Hao, Zhenkai; Suo, Jingxia; Yu, Yonglan; Suo, Xun; Liu, Xianyong (Frontiers in Microbiology, 2023)
The antiparasitic drug halofuginone is important for controlling apicomplexan parasites. However, the occurrence of halofuginone resistance is a major obstacle for it to the treatment of apicomplexan parasites. Current studies have identified the molecular marker and drug resistance mechanisms of halofuginone in Plasmodium falciparum. To explore resistance mechanisms of halofuginone in Eimeria tenella, here we used transcriptomic data from both halofuginone sensitive and resistant strains treated with halofuginone to explore the differences in gene expression profiles. Hundreds of differentially expressed genes (DEGs) were detected among sensitive groups after treatment with different drug concentrations, whereas only 12 DEGs were detected in the resistant group before and after halofuginone treatment. In the sensitive group, DEGs associated with enzymes were significantly downregulated, whereas the DNA damaging process was upregulated after halofuginone treatment, revealing the mechanism of halofuginone-induced parasite death. In addition, the DEGs related to translation were significantly downregulated after halofuginone induction. Overall, our results provide a gene expression profile for further studies on the mechanism of halofuginone resistance in E. tenella.